The importance of diet in the epidemiology of cancer of the colon and rectum - Lopes, Eliza da Conceição da Fonseca; Derivi, Sandra Casa Nova; Mendez, Maria Heidi Marques (Revista de Saúde Pública, 1984)
Studies have been made to verify the relation between the environmental factor, diet rich in fat and deficient in fibre, and the epidemiologic distribution of cancer of the colon and rectum. The research emphasizes the differences between the diets of the industrialized and the developing countries, and the influence of religion and migratory movements on the diet usualy associated with incidence of the disease.